A LIFE-STAGE APPROACH FOR DECOMPOSING SPATIOTEMPORAL POPULATION CHANGES ALONG AN URBAN-RURAL GRADIENT: IMPLICATIONS FOR REGIONAL PLANNING. Issue 1 (1st January 2023) - Gurrutxaga, Mikel
Abstract: The study of population changes across space and time of cohorts at different life stages is relevant for regional planning, but it is often not taken into account. We focus on a case study along the urban-rural gradient of continental Spain from 2002 to 2017 at a municipal scale. Making use of longitudinal data from the municipal registers, we studied changes in total population and three birth cohorts: the cohort joining the workforce, the cohort at a mature working age and the cohort reaching retirement during the study period. The results showed key spatiotemporal population variations. The absolute population increased in 36% of the municipalities, but at least one of the study cohorts showed an increase in 75% of the municipalities. While the cohort joining workforce tended to concentrate in urban and suburban areas, the retiring cohort tended to move to small suburban and rural municipalities. In the next decades the retirement of large birth cohorts in Spain will be a relevant issue for planning. This methodological approach allows us to understand life cycle residential movements across urban, suburban and rural areas and better enables spatial planning decisions. The method can be applied to other study areas at different spatial and temporal scales.